2002
DOI: 10.1111/j.1349-7006.2002.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Glucose Transporter 1 (GLUT1) Expression in Human Breast Carcinoma

Abstract: Glucose uptake and glycolytic metabolism are enhanced in cancer cells compared to normal cells and tissues. Increased expression of glucose transporter 1 (GLUT1) has been reported in human malignant cells. The aim of this study is to determine the expression of the facilitative glucose transporter protein GLUT1 in human breast carcinomas and a possible correlation between GLUT1 expression and clinical outcome including disease-free or overall survival. One hundred consecutive formalin-fixed, paraffin-embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 22 publications
(18 reference statements)
5
102
0
Order By: Relevance
“…GLUT1 expression in tumors also correlates with the survival of patients. In lung, colorectal, ovarian, laryngeal, and breast carcinomas, high levels of GLUT1 or GLUT3 in the tumors were significant indicators of decreased survival (Baer et al, 1997;Ogawa et al, 1997;Younes et al, 1997;Haber et al, 1998;Cantuaria et al, 2001;Kang et al, 2002). GLUT1 staining has also been identified in 25% of hyperplastic breast tissue and 25% of histologically normal breast tissue adjacent to tumors (Alo et al, 2001).…”
Section: Glut Expression In Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…GLUT1 expression in tumors also correlates with the survival of patients. In lung, colorectal, ovarian, laryngeal, and breast carcinomas, high levels of GLUT1 or GLUT3 in the tumors were significant indicators of decreased survival (Baer et al, 1997;Ogawa et al, 1997;Younes et al, 1997;Haber et al, 1998;Cantuaria et al, 2001;Kang et al, 2002). GLUT1 staining has also been identified in 25% of hyperplastic breast tissue and 25% of histologically normal breast tissue adjacent to tumors (Alo et al, 2001).…”
Section: Glut Expression In Tumorsmentioning
confidence: 99%
“…GLUT1 expression in breast cancer has also been studied extensively (Brown and Wahl, 1993;Younes et al, 1995;Brown et al, 1996;Binder et al, 1997;Alo et al, 2001;Avril et al, 2001;Bos et al, 2002;Brown et al, 2002;Kang et al, 2002;Ravazoula et al, 2003). GLUT1 expression has been correlated with a number of tumor characteristics.…”
Section: Glut Expression In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung and ovarian tumor, comparative increase in GLUT1 expression was observed in cancer patients with higher grade of malignancy, higher proliferative index and lower degree of differentiation [111,112]. Consistently, GLUT1 expression level reciprocally correlates with survival rate of cancer patients [112][113][114]. Since the expression and regulation of GLUTs are tissue and often cell-specific, expression of some isoforms may only be observed in tumor cells but absent in normal cells.…”
Section: Augmented Glucose Uptakementioning
confidence: 74%
“…Because GLUT1 was exclusively found in human breast cancer biopsies and its expression was strongly associated with tumor grade, proliferation as well as invasiveness [111,120,121], GLUT1 has been proposed to be a new marker for diagnosis and prognosis of human breast cancers, an indication of tumor aggressiveness, and a possible therapeutic target for patients with breast cancer [114,175]. It has been demonstrated that drug mediated inhibition of glucose transport in-creased the effectiveness of several anti-tumor drugs and effectively induced growth arrest and apoptosis in lung, breast cancer and leukemia cell lines [175,176].…”
Section: Gluts As a Target Of Metabolic Therapymentioning
confidence: 99%